Disfunción familiar y rendimiento académico de los estudiantes de la Unidad Educativa Guillermo Herrera Sánchez, parroquia Taquil, en la actualidad - Salinas Correa, Edison Fabián (2025)
The research has a research perspective in human and social sciences based on the relationship between family dysfunction and academic performance. Its general objective is to analyze the influence of family dysfunction on academic performance in the Guillermo Herrera Sanchez Educational Unit, Taquil parish, at present. And which in turn is guided by the following specific objectives: to provide a theoretical basis for family dysfunction and academic performance, through a literature review, to determine the relationship between family dysfunction and academic performance in the Guillermo Herrera Sanchez Educational Unit, Taquil parish, in the period 2023 - 2024, and to propose an intervention proposal to strengthen the family bond and improve the academic performance of students. The research was conducted under the methodological approach, which was chosen according to the nature of the data as a mixed method, in order to analyze the impact of family dysfunction on academic performance. Regarding the method, the following were used: inductive and deductive. The techniques used were: documentary analysis, survey, interview. The following instruments were used: the APGAR dysfunction test. The sample was represented by 60 students and 8 teachers of the institution. The results of the analysis of the relationship of variables show that the 26 students who presented problems of severe family dysfunction. The results of the analysis of the relationship of variables mention that the 26 students who presented problems of severe family dysfunction, 16 reached the required learning since they are in the ranges between 7 to 8.99, and thus we can deduce that in terms of grades the level of dysfunction does not affect this part of the academic performance. Finally, students with severe dysfunction are close to reaching the required learning (range 4.01 to 6.99), affecting their academic performance. It is observed that there is a minimal statistical relationship between the variable’s family dysfunction and low performance